2017
DOI: 10.1186/s12879-017-2845-3
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal arthritis and myopericarditis: a case report

Abstract: BackgroundWe report the first adult case of Neisseria meningitidis W-135 presenting with meningococcal arthritis and myopericarditis concomitantly, without other classical features of meningococcal disease.Case presentationA 67-year-old Caucasian man presented with acute-onset polyarthralgia, myalgia, and fever. On examination he had polyarticular synovitis. An electrocardiogram (ECG) demonstrated ST-elevation in leads I, II, III, aVF, and V2-V6 without reciprocal depression, and a high-sensitivity troponin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…As with more recognised forms of septic arthritis, the knee is the most commonly affected joint, but there have been two other reported cases in the literature of PMA originating in a native ankle joint 2 4. The most common causative serotype in adults is Group B,10 and to our knowledge, there have only been two other cases, in the adult population, caused by the Group W serotype 10 11. Although she had previously received the full programme of vaccinations against meningococcal disease, it has been reported that the efficacy of the meningococcal conjugate vaccine (MenACWY, covering the Group W serotype) decreases after the first year 12…”
Section: Discussionmentioning
confidence: 81%
“…As with more recognised forms of septic arthritis, the knee is the most commonly affected joint, but there have been two other reported cases in the literature of PMA originating in a native ankle joint 2 4. The most common causative serotype in adults is Group B,10 and to our knowledge, there have only been two other cases, in the adult population, caused by the Group W serotype 10 11. Although she had previously received the full programme of vaccinations against meningococcal disease, it has been reported that the efficacy of the meningococcal conjugate vaccine (MenACWY, covering the Group W serotype) decreases after the first year 12…”
Section: Discussionmentioning
confidence: 81%
“…PMSA is most often monoarthritic, affecting either the knee or ankle joint 16–20. It occurs in <3% of meningococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the alarming increase in the number of meningococcal W infections, it is important that physicians become more aware of unusual presentations of meningococcal disease such as PMSA. With prompt diagnosis and initiation of treatment, the prognosis is excellent 20…”
Section: Discussionmentioning
confidence: 99%